x=-1
becaus:
12x+3=2x-7
10x+3=-7 (-2x)
10x=-10 (-3)
x=-1 (divided by 10)
12x = x + 3 11x = 3 x = 3/11
x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0
8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5
12x - 8 = 10x + 42x = 12x = 6
(2x + 3)(2x + 3)
12x = x + 3 11x = 3 x = 3/11
x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0
5x-3 = 11+12x 5x-12x = 11+3 -7x = 14 x = -2
8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5
12x - 8 = 10x + 42x = 12x = 6
There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.
(2x + 3)(2x + 3)
This is not an inequality. This is an equation.12x+7=43 12x=36 x=3
4x2 = -12x, divide both sides by 4x: x = -3
12x-3=2x+17 10x-3=17 10x=20 x=2
-3/2
2x + 3 = -92x = -12x = -6